2021
DOI: 10.1007/s00268-021-06159-4
|View full text |Cite
|
Sign up to set email alerts
|

Infrahepatic Inferior Vena Cava Clamping does not Increase the Risk of Pulmonary Embolism Following Hepatic Resection

Abstract: Background Infrahepatic inferior vena cava (IVC) clamping reduces central venous pressure. However, controversies remain regarding its impact on postoperative complications, particularly, the incidence of postoperative pulmonary embolism (PE). The aim of the study was to determine the impact of IVC clamping on the incidence of PE in patients undergoing hepatectomy. Methods A pooled analysis of five prospective trials on patients who underwent hepatic resec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 48 publications
1
3
0
Order By: Relevance
“…Patients in the study group achieved significantly higher MMES scores than those in the control group at postoperative 1 day, 3 days and 7 days (p < 0.05). These results were consistent with previous studies [29,30], which further confirmed the advantage of controlled low central venous pressure combined with dexmedetomidine during laparoscopic hepatectomy resection.…”
Section: Discussionsupporting
confidence: 93%
“…Patients in the study group achieved significantly higher MMES scores than those in the control group at postoperative 1 day, 3 days and 7 days (p < 0.05). These results were consistent with previous studies [29,30], which further confirmed the advantage of controlled low central venous pressure combined with dexmedetomidine during laparoscopic hepatectomy resection.…”
Section: Discussionsupporting
confidence: 93%
“…However, a recent meta-analysis confirmed that IVC-clamping is not associated with increased incidence of PPE in OLR. 4 In this study, we did not observe any case of PPE. Compared to other studies performing LLR without IVC-clamping, our results showed no potential risk or increased morbidity and mortality.…”
Section: Discussionmentioning
confidence: 43%
“…This might be due to heterogenous application of SBRT techniques between institutions, including the shift to hypofractionation from three to five fractions over time, as well as the use of heterogenous SBRT doses, and the results should be considered therefore cautiously. Moreover, the lack of data on known prognostic variables such as patients’ liver function treatment-associated toxicity and postoperative liver surgery complications [ 47 , 48 , 49 ], as well as the number and location of lesions (i.e., centrally located tumors with potential vascular invasion), and other second-line treatments after primary surgery or SBRT needs to be mentioned as a limitation of our study that might have introduced bias. Further, there are no data on the treatment of recurrent disease or data on local tumor control.…”
Section: Discussionmentioning
confidence: 99%